Key elements in the development of framework for post-flood disaster waste management in Malaysia / Nor Syazwani Yusof - Yusof, Nor Syazwani (2018)
Malaysia is one of the chosen developed countries that hits by extreme flood in December 2014. Due to urbanisation, population growth, and economic development increases leading to larger quantities of flood waste. There are some actions been taken by the government but the results has not been translated in the proper guidelines of strong legal instruments and enforcement. Lack of managing of flood waste practicing and less of special skills on managing flood waste is one of the problems to Malaysia in reducing environmental impacts and dumping areas.